A MALAYSIAN PERSPECTIVE ON DECOLONIZATION: LESSONS FOR INDONESIA? - Lindblad, J. Thomas (Masyarakat Indonesia, 2013)
The great regime change in Indonesian history, represented by independence and decolonization, had profound implications for the state apparatus, in particular in its relationship to the economy. This contribution seeks to widen our perspective on such change in Indonesia by reviewing evidence from the experience of adjacent Malaysia. Particular attention is given to the indigenization of the government bureaucracy - Indonesianisasi in Indonesia, Malayanization in Malaysia - before as well as in the immediate aftermath of independence. Our findings underscore the recent consensus in the international literature that the way in which the process of decolonization occurred had enormous consequences for subsequent performance. This article argues that Indonesia could have reaped considerable benefit if in a position to apply the Malaysian model of indigenizing the institution of the state.